2016
DOI: 10.7717/peerj.2300
|View full text |Cite
|
Sign up to set email alerts
|

Minimum information about tolerogenic antigen-presenting cells (MITAP): a first step towards reproducibility and standardisation of cellular therapies

Abstract: Cellular therapies with tolerogenic antigen-presenting cells (tolAPC) show great promise for the treatment of autoimmune diseases and for the prevention of destructive immune responses after transplantation. The methodologies for generating tolAPC vary greatly between different laboratories, making it difficult to compare data from different studies; thus constituting a major hurdle for the development of standardised tolAPC therapeutic products. Here we describe an initiative by members of the tolAPC field to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…The difficulty in comparing the characteristics of different clinical tDC does suggest the need for an uniform set of metrics for their description. This was the focus of the minimum information about tolerogenic antigen-presenting cells ( 103 ) initiative whose authors included members from a number of the completed and ongoing clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in comparing the characteristics of different clinical tDC does suggest the need for an uniform set of metrics for their description. This was the focus of the minimum information about tolerogenic antigen-presenting cells ( 103 ) initiative whose authors included members from a number of the completed and ongoing clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum information about tolerogenic antigen-presenting cells (MITAP) checklist (32) was followed for the preparation of this manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…As there are diverse methods of generating tolDCs and other types of tolerogenic APC (tolAPCs), a minimum information model for tolAPC (MITAP) was generated. MITAP enables researchers to report their data in a standardized and more transparent manner, facilitating data comparison and interpretation, ultimately paving the way for the development of standardized protocols for the production of tolDCs and other tolAPCs for therapeutic application . A number of tolDCs have been tested in phase I clinical trials, including for type I diabetes, Crohn's disease and RA .…”
Section: Tolerogenic Dendritic Cells As a Therapeutic Toolmentioning
confidence: 99%
“…MITAP enables researchers to report their data in a standardized and more transparent manner, facilitating data comparison and interpretation, ultimately paving the way for the development of standardized protocols for the production of tolDCs and other tolAPCs for therapeutic application. 38 A number of tolDCs have been tested in phase I clinical trials, including for type I diabetes, 30 Crohn's disease 39 and RA. 40,41 Encouragingly, tolDC therapy in all these studies was found to be feasible and safe, providing rationale to conduct further studies into their efficacy.…”
Section: Tolerogenic Dendritic Cells As a Therapeutic Toolmentioning
confidence: 99%